Analysis of herbicide biosorption by means of a phenomenological mathematical distributed parameter model. Issue 13 (7th June 2022) - Wernke, Gessica; Triques, Carina Contini; Suzaki, Pedro Yahico Ramos; Fagundes-Klen, Márcia Regina; Bergamasco, Rosângela
ABSTRACT: A distributed parameter model and two lumped parameter models were used in order to find the rate-limiting step in the adsorption process of a herbicide (Diuron) by Moringa oleifera husks, a possible low-cost adsorbent. For that, four kinetics assays, differentiated by the initial Diuron concentration, were performed. Langmuir isotherm well represented the equilibrium data and through this evaluation, Moringa husks proved to be a potential adsorbent for Diuron removal from water. The internal mass transfer resistance, analysed as a distributed parameter model, was found to better represent the experimental data. This fact enabled the simulation of the process according to the variation of time and space, which contributed to the better understanding of the adsorption process. GRAPHICAL ABSTRACT: UF0001